Hubungan Berat Plasenta dengan Status Antropometri Bayi baru Lahir Aterm Wilayah Puskesmas Kassi-Kasi Makassar - Rahman, Fath Irtaniyah; Patimah, Sitti; Kurnaesih, Een (Window of Health : Jurnal Kesehatan, 2018)
The phenomenon of sexual intercourse in women Premenopausal In Makassar city birth weight infants depends on the nutrition of mother and placenta's ability to transport nutrients from mother to fetus. The weight of the placenta, and the size and shape of the surface, reflecting its ability to transfer nutrients. The weight of the placenta is a measure commonly used to summarize the growth and function of the placenta. This research aims to analyze the relationship of the weight of the placenta with a status of newborn Anthropometry term. Type of this research is descriptive analytic with a cross-sectional design. The number of samples in this study was 59 people mother intrapartum taken by way of Simple Random Sampling. Data analysis was done with the chi-square test, with a confidence level of Î± = 0.05. Based on the results of this research noted that the value of significance p = 0,013 birth weight (p < 0.05), birth length p = 0.00 (p < 0.05), head circumference p = 0,010 (p < 0.05), the ratio of the weight of the placenta the normal 46 people (78%) abnormal 13 people (8.5%), and index ponderal baby normal 54 people (91.5%) and not normal 5 people (8.5%). Thus it can be concluded that there is a relationship between the weight of the placenta with a status of Anthropometry weight born babies, birth, body length and head circumference, but not with the ratio of the weight of the placenta and baby ponderal index